Infraocclusion: Dental development and associated dental variations in singletons and twins. Issue 9 (September 2015) - Odeh, Ruba; Townsend, Grant; Mihailidis, Suzanna; Lähdesmäki, Raija; Hughes, Toby; Brook, Alan
Highlights The prevalence of dental variations in children with infraocclusion was investigated. Dental development was delayed and tooth size reduced in those with infraocclusion. Ectopic canines and lateral incisor complex were associated with infraocclusion. The primary canines were significantly smaller in the infraoccluded group.